COMPARISON OF ORAL DOXYCYCLIN EWITH ORAL MONTELUKAST IN THE TREATMENT OF MODERATE ACNE VULGARIS - Aslam, Memoona; Raza, Naeem; Nadeem, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare oral Montelukast with oral Doxycycline in the treatment of moderate Acne Vulgaris in terms of mean change in acne severity index. Study Design: Quasi-experimental study.Place and Duration of Study: Department of Dermatology, Pak Emirates Military Hospital Rawalpindi, from Mar 2016 to Aug 2016.Methodology: A total of 84 patients were included in the study. They were randomly assigned to group A and B by consecutive non probability sampling technique. Group A was given 100mg Doxycycline with topical 10% benzoyl peroxide and group B was given 5mg Montelukast with topical 10% benzoyl peroxide. Acne severity index (ASI) was calculated at base line and after one month. Mean change in acne severity index was observed for both the groups.Results: Independent sample t-test was used to compare the means. Mean post treatment change in acne severity index of group A was 5.45 ± 1.29 and group B was 1.80 ± .59 respectively (p-value